2007
DOI: 10.1007/s12149-007-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MET-PET and FDG-PET for differentiation between benign lesions and lung cancer in pneumoconiosis

Abstract: Our results indicate that nodules with an intense uptake of MET and FDG relative to their size should be carefully observed because of a high risk for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…The SUV in the granuloma was significantly lower than that in the tumor (Fig. 6c), which is consistent with the previous reports [15,30]. Thus, the dynamic pattern of 11 C-MET uptake was significantly different between tumors and granulomas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The SUV in the granuloma was significantly lower than that in the tumor (Fig. 6c), which is consistent with the previous reports [15,30]. Thus, the dynamic pattern of 11 C-MET uptake was significantly different between tumors and granulomas.…”
Section: Discussionsupporting
confidence: 91%
“…Our clinical study [15] also showed that the SUV max of 11 C-MET was significantly higher in lung cancer than in the pneumoconiotic nodules. Inflammatory processes, however, can result in an increased uptake level of 11 C-MET in certain brain regions after stereotactic radiosurgery and be mistaken for residual tumor tissue [16].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…It was reported the 18 F-FDG and 11 C-methionine have sensitivity of 60% and 80% and specificity of 100% and 93%, respectively, for identification of lung cancer. 81 As stated earlier, it has been reported that dualtime point 18 F-FDG-PET can provide better discrimination of benign and malignant lung nodules and pleural changes when compared with that using structural imaging. 72,82 Thus, FDG-PET might have some role in pneumoconiosis diagnostic or prognostic monitoring, but much more clinical evaluation is required.…”
Section: Nononcologic Applicationsmentioning
confidence: 81%
“…In a comparative study of the ability of C 11 methionine (MET) and FDG-PET to diagnose lung cancer in patients with pneumoconiosis, Kanegae et al [19] examined 26 subjects who underwent both whole-body MET-PET and FDG-PET on the same day. The first group was a lung cancer group, which consisted of 15 patients, including those with pneumoconiosis with multiple nodules (13 cases), hemoptysis (one case), and positive sputum cytology (one case).…”
Section: Occupational Pleuropulmonary Disordersmentioning
confidence: 99%